A hybrid controller for PWM active rectifiers based LCL filters. Issue 4 (6th July 2015) - Marzouki, Amira; Hamouda, Mahmoud; Fnaiech, Farhat
Abstract : Purpose: – The purpose of this paper is to propose a new hybrid control method of pulse width modulation (PWM) active rectifiers tied to the grid through an LCL filter. The control method is designed with the aim to achieve a perfect regulation of the dc-bus voltage; a near unity input power factor (UIPF) operation as well as a high quality of the line currents. Design/methodology/approach: – The proposed hybrid control method consists of a PI-based linear controller cascaded with a nonlinear one. The nonlinear controller (inner loop) is designed using the input-output feedback linearization (IOFL) theory. It should control both the dc-bus voltage and the input currents at the converter's poles. The linear controller (outer loop) is devoted to control the reactive line current so as to achieve a near UIPF. Findings: – A perfect regulation of the dc-bus voltage and a near UIPF operation are achieved. Moreover, a high quality of the line currents is obtained. The robustness and effectiveness of the proposed control method have been successfully tested under variation of the dc voltage reference as well as grid and load disturbances. Practical implications: – The proposed method is useful for single-stage and two-stage grid connected photovoltaic systems, wind energy conversion, and distributed power generation systems. Originality/value: – The main novelty of this paper is the combination of linear and nonlinear controllers with the aim to control a PWM active rectifier tied to the grid through a third-order LCL filter. In the opinion, such control method has not been applied to this converter in earlier research papers. The numerical simulations carried out under normal and abnormal conditions confirm the effectiveness of the proposed approach.